Effect of hydrogel-based antibiotic intracanal medicaments on crown discoloration - Rayan B. Yaghmoor; Jeffrey A. Platt; Kenneth J. Spolnik; Tien Min Gabriel Chu; Ghaeth H. Yassen (Restorative Dentistry & Endodontics)
ObjectivesThis study evaluated the effects of low and moderate concentrations of triple antibiotic paste (TAP) and double antibiotic paste (DAP) loaded into a hydrogel system on crown discoloration and explored whether application of an adhesive bonding agent prevented crown discoloration.Materials and MethodsIntact human molars (n = 160) were horizontally sectioned 1 mm apical to the cementoenamel junction. The crowns were randomized into 8 experimental groups (calcium hydroxide, Ca[OH]2; 1, 10, and 1,000 mg/mL TAP and DAP; and no medicament. The pulp chambers in half of the samples were coated with an adhesive bonding agent before receiving the intracanal medicament. Color changes (ΔE) were detected by spectrophotometry after 1 day, 1 week, and 4 weeks, and after 5,000 thermal cycles, with ΔE = 3.7 as a perceptible threshold. The 1-sample t-test was used to determine the significance of color changes relative to 3.7. Analysis of variance was used to evaluate the effects of treatment, adhesive, and time on color change, and the level of significance was p < 0.05.ResultsCa(OH)2 and 1 and 10 mg/mL DAP did not cause clinically perceivable tooth discoloration. Adhesive agent use significantly decreased tooth discoloration in the 1,000 mg/mL TAP group up to 4 weeks. However, adhesive use did not significantly improve coronal discoloration after thermocycling when 1,000 mg/mL TAP was used.ConclusionsCa(OH)2 and 1 and 10 mg/mL DAP showed no clinical discoloration. Using an adhesive significantly improved coronal discoloration up to 4 weeks with 1,000 mg/mL TAP.